2015
DOI: 10.1155/2015/630482
|View full text |Cite
|
Sign up to set email alerts
|

Polysulfated Trehalose as a Novel Anticoagulant Agent with Dual Mode of Action

Abstract: Physiological hemostatic balance is a coordinated outcome of counteracting coagulation and fibrinolytic systems. An imbalance of procoagulant and anticoagulant factors may result in life threatening thromboembolism. Presently, anticoagulant administration is the first line of therapy for the treatment of these conditions and several anticoagulants have been approved, including various forms of heparin. However, the polyanionic nature and multispecificity of heparin pose several complications. Generally, the po… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 43 publications
(36 reference statements)
0
6
0
Order By: Relevance
“…found that the commercially available sucrose octasulfate ( 18 ) directly inhibits thrombin with high potency but low efficacy after binding with exosite II of thrombin . Jairajpuri and co‐workers synthesized trehalose octasulfate ( 19 ) as a dual anticoagulant/antiplatelet agent but the mechanism of action was not fully elucidated …”
Section: Heparin Mimeticsmentioning
confidence: 99%
“…found that the commercially available sucrose octasulfate ( 18 ) directly inhibits thrombin with high potency but low efficacy after binding with exosite II of thrombin . Jairajpuri and co‐workers synthesized trehalose octasulfate ( 19 ) as a dual anticoagulant/antiplatelet agent but the mechanism of action was not fully elucidated …”
Section: Heparin Mimeticsmentioning
confidence: 99%
“…Activated partial thromboplastin time (APTT), prothrombin time (PT), and thromboplastin time (TT) clotting assays were performed by utilizing commercially available kits and in accordance with the manufacturer's instructions. All the experiments were performed by the previously described protocol [ 22 , 23 ]. Each test run was repeated three times with 175 nM of wtPDI and its variants were used during the clotting time experiments, where the protein was added exogenously.…”
Section: Methodsmentioning
confidence: 99%
“…109,110 Several natural products in their fully or partially sulfated forms have now been evaluated as anti-coagulants. These include sulfated quercetins, 111 sulfated trehalose, 112 and sulfated esculin. 113 Of these, the latter has been shown to be selective for AT over HCII and is sufficiently functional in reducing thrombus formation in the rat model of venous thrombosis.…”
Section: ■ Synthetic Sulfated Inhibitors Of Coagulation Factorsmentioning
confidence: 99%